EBV epigenetically suppresses the B cell-to-plasma cell differentiation pathway while establishing long-term latency. - Christine T Styles; Quentin Bazot; Gillian A Parker; Robert E White; Kostas Paschos; Martin J Allday (PLoS Biology)
Mature human B cells infected by Epstein-Barr virus (EBV) become activated, grow, and proliferate. If the cells are infected ex vivo, they are transformed into continuously proliferating lymphoblastoid cell lines (LCLs) that carry EBV DNA as extra-chromosomal episomes, express 9 latency-associated EBV proteins, and phenotypically resemble antigen-activated B-blasts. In vivo similar B-blasts can differentiate to become memory B cells (MBC), in which EBV persistence is established. Three related latency-associated viral proteins EBNA3A, EBNA3B, and EBNA3C are transcription factors that regulate a multitude of cellular genes. EBNA3B is not necessary to establish LCLs, but EBNA3A and EBNA3C are required to sustain proliferation, in part, by repressing the expression of tumour suppressor genes. Here we show, using EBV-recombinants in which both EBNA3A and EBNA3C can be conditionally inactivated or using virus completely lacking the EBNA3 gene locus, that-after a phase of rapid proliferation-infected primary B cells express elevated levels of factors associated with plasma cell (PC) differentiation. These include the cyclin-dependent kinase inhibitor (CDKI) p18INK4c, the master transcriptional regulator of PC differentiation B lymphocyte-induced maturation protein-1 (BLIMP-1), and the cell surface antigens CD38 and CD138/Syndecan-1. Chromatin immunoprecipitation sequencing (ChIP-seq) and chromatin immunoprecipitation quantitative PCR (ChIP-qPCR) indicate that in LCLs inhibition of CDKN2C (p18INK4c) and PRDM1 (BLIMP-1) transcription results from direct binding of EBNA3A and EBNA3C to regulatory elements at these loci, producing stable reprogramming. Consistent with the binding of EBNA3A and/or EBNA3C leading to irreversible epigenetic changes, cells become committed to a B-blast fate <12 days post-infection and are unable to de-repress p18INK4c or BLIMP-1-in either newly infected cells or conditional LCLs-by inactivating EBNA3A and EBNA3C. In vitro, about 20 days after infection with EBV lacking functional EBNA3A and EBNA3C, cells develop a PC-like phenotype. Together, these data suggest that EBNA3A and EBNA3C have evolved to prevent differentiation to PCs after infection by EBV, thus favouring long-term latency in MBC and asymptomatic persistence.